(3GdJMcje aj GdeYGedGJ GdeGdjI GdOGNdjI h GdOhdjI GdeOfjI h GdJLGQjI h GdGOGQjI h GdLeQcjI h GdVQjHjI (B:s (3OQGSI ebGQfI (B/s - (3SdGeI, CMeO YHO GdcQjes ((3GdbGgQI(B: s (3OGQ GdfgVI GdYQHjI(B, s, 2006)
(3eGgjI GdJMcje h VQhQJg h GdGgJeGe Hg eGgjI GJaGb GdJMcje h GdbGfhf hGLH GdJWHjb Ydi GJaGb GdJMcje h fWGb GdbGfhf hGLH GdJWHjb Ydi GJaGb GdJMcje , GdbGfhf hGLH GdJWHjb Ydi GLQGAGJ GdJMcje h JTcjd gjFI GdJMcje , ELQGAGJ NUheI GdJMcje (B.s
Keywords: (3GdEbJUGOs; (3GdJMcjes; (3GdbGfhfs